Balancing Climate Justice with Sustainable Development Needs in A Policy: Questioning about Government Regulations for National Strategic Projects Facilitation - Anggraeni , Ricca (Universitas Kuningan, 2024)
The problem is that Government Regulation Number 42 of 2021 on National Strategic Projects Facilitation deals with the concepts of environmental balance and climate change policy. Spatial planning, including marine space, land acquisition, and forestry, should support national strategic projects. On the one hand, the environmental balance must be maintained to mitigate global warming. Government Regulation on National Strategic Projects Facilitation is like a two-edged knife; the balance point must be found so that climate justice and sustainable development can be achieved. Through normative research methods with qualitative data analysis, it was discovered that Government Regulation on National Strategic Projects Facilitation, on the one hand, succeeded in becoming an infectious engine for infrastructure development and development for the welfare of the community, but on the other hand, Government Regulation became a suppressive engine for the community group, the living environment, and spatial balance. Government Regulation on National Strategic Projects Facilitation is not yet on the side of the people and communities most vulnerable to the impact of climate change due to the development of the National Strategic Projects infrastructure to pursue the achievement of the SDGs. Therefore, the pattern of government regulation on national strategic projects facilitation must change, not only to “increase the number of infrastructure developments” but also to improve the quality of human life today and in the future, so that access to SDGs in Indonesia becomes something comprehensive because it does not interfere with achieving other indicators.